Botulinum toxin in the treatment of patients with myofascial pain: a scoping review (Research, Society and Development, 2023)
Temporomandibular disorders (TMD) can be classified as alterations that affect the temporomandibular joint, the masticatory muscles, and associated structures, being divided into two large groups: TMD of muscular origin and joint origin, being those of muscular origin more frequent. Despite existing studies, the etiology and treatment of these alterations have not yet been fully clarified, and among the treatment modalities, the use of botulinum toxin type A (TXA) in myofascial pain, a TMD of muscular origin, has been discussed. This study aims to review the literature on the effectiveness of using TXA for the treatment of myofascial pain. A search was carried out in the PubMed and SciELO databases using the descriptors “Botulinum Toxin”, “Temporomandibular” and “Myofascial Pain”, from 2012 to 2022. One hundred sixty-seven articles were found, but only 11 met the established inclusion criteria. It was observed that the use of TXA for the treatment of myofascial pain proved to be, in most studies, equally effective when compared to other less invasive treatment methods, but there are still few studies on the subject, especially randomized controlled clinical trials. Therefore, more randomized controlled trials with high methodological rigor and long-term follow-up are needed to support the indication of TXA in the treatment of TMD-related myofascial pain.